Bacteriological profile, antimicrobial susceptibility, and factors associated with urinary tract infection in pregnant women - Taha, Aza B (The Journal of Infection in Developing Countries, 2024)
Introduction: Urinary tract infection (UTI) is a common bacterial complication in pregnancy. The study aimed to estimate the prevalence, risk factors, and bacterial etiology of UTI during pregnancy and determine the efficacy of antimicrobial drugs in treating UTIs. Methodology: Urine specimens and clinical data were collected from pregnant women who attended primary health centers in Erbil, Iraq. All specimens were cultured on appropriate media and identified by standard microbiological methods. The pregnant women were grouped into symptomatic UTI group, asymptomatic bacteriuria group, and the control group. The agar dilution method was used to determine antimicrobial susceptibility. Results: Among the 5,042 pregnant women included in this study, significant bacteriuria was found in 625 (12.40%) of the cases, and 198 (31.68%) had symptomatic UTI, of which 43.59% were diagnosed during the third trimester. Out of the 643 bacteria isolated, 33.28% were symptomatic UTI, of which 43.59% developed during the third trimester. There was a significant difference in the bacterial etiology between symptomatic UTI and asymptomatic bacteriuria (p = 0.002), as well as between cystitis and pyelonephritis (p = 0.017). The most common bacterial species isolated was Escherichia coli, which was susceptible to fosfomycin (100%), meropenem (99.45%), and nitrofurantoin (97.8%). Conclusions: Pregnant women are more likely to develop UTI in the third trimester. Escherichia coli is the predominant pathogen. The study suggests the use of fosfomycin, meropenem, and nitrofurantoin for the treatment of UTI. No Gram-positive isolates were resistant to daptomycin.